Evaluasi Dampak Upah Minimum Regional dan Indeks Pembangunan Manusia terhadap Reduksi Tingkat Kemiskinan di Jawa Barat 2019-2023 - Abdul Aziz; Abdul Husenudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The high level of poverty in West Java is a significant obstacle in the context of economic development efforts in this province. The problem of poverty is a serious focus that must be addressed by regional governments, considering that this reflects the level of community welfare at the regional level. The negative impacts of poverty show significant variations, include serious social problems, and have the potential to affect development progress in a region or country. This analysis uses panel data analysis, which is a combination of cross section and time series data. There are 3 methods used to estimate panel data regression analysis models, namely: Random Effect Model, Fixed Effect Model, and Common Effect Mode. Test methods such as the Chow test, Hausman test, and Lagrange Multiplier test. Then a classical assumption test is carried out and ends with a hypothesis test. The regional minimum wage (UMR) partially has a probability of 0.000 which is lower than 0.10 and the calculated t value of the regional minimum wage variable is greater than the t table value (5.413282 > 2.05183), indicating that the regional minimum wage has a positive and significant influence towards reducing poverty levels in West Java Province. Meanwhile, the results of the analysis show a coefficient value of -3.045716, indicating that there is a significant negative influence between the human development index (HDI) and the poverty level in West Java Province